Competitive performance rating criteria in elite biathlon - Batalov, A. G.; Jilkibaeva, N. Zh. (Theory and Practice of Physical Culture, 2018)
Objective of the study was to estimate the competitive performance of the winners and runner-ups (referred to herein as the Global Elite) of the top-ranking international events including World Cups, World Championships and Olympic Games in the period of 2006 to 2017; versus that of the top three national athletes (Russian Elite). The competitive performance rating criteria were as follows: speed coefficient (SC) - the measure of speed of the athlete, describing the time loss in seconds from the fastest athlete per one kilometer; shooting percentage (SP); and shooting time meaning total time on the shooting range. For the purposes of the study the official competitive protocols of the events were examined. Comparative analyses of studied parameters of the Global Elite and Russian Elite showed that the national best athletes lose mostly in the shooting percentage (SP) value for the male group and in the racing speed for the female one.